Benefits for the father from their involvement in the labour and birth sequence - Coutinho, Emília Carvalho (2017)
The link between father and child is fundamental, the presence of the former in the birthing room being essential to closer links between the triad. The purpose of this study is to identify the benefits for the father from their involvement during the labor and birth sequence. An integrational review of the literature was carried out together with research on the databases: PubMed, LILACS, SciELO, Institutional Holdings and Digital Libraries and EBSCO Host published between 2000 e 2014. The results demonstrate the existence of a ‘new’ father who is involved in the consultations during the pregnancy and preparations for the birth, his presence in the birthing room making him feel that he is playing an active part in the process encourages him to develop closer and more intimate links leading to a consolidation of the family unit, the assumption of a parental role in addition to being able to share the experience of the birth with the mother and contribute to her well-being. The team of health professionals has a crucial role in the integration of the father into the process of maternity with his presence also being reflected in the humanization of health care. It may be concluded that there are many benefits from paternal involvement in the birth when accompanying the mother from the moment of pregnancy with an active presence during the birth and enjoying the entire process by sharing emotions and feelings and contributing to the humanization of care and an affective link between the triad. The performance of the Specialist Nursing Staff in the areas of Maternal health and Obstetrics is reflected in the inclusion of the father in the birthing room and in the de-mythification of taboos.